Compressive Strength of Mineral Trioxide Aggregate with and without Disodium Hydrogen Phosphate at Different Mixing Ratios - Mokhtari, Hadi; Lotfi, Mehrdad; Mozafari, Aysan; Rahbar, Mahdi; Sohrabi, Aydin; Tadbiri, Ayda (Iranian Endodontic Journal, 2018)
Introduction: Mineral Trioxide Aggregate (MTA) is a substance with favorable physical-mechanical properties. Disodium hydrogen phosphate(DHP) is sometimes added to MTA to reduce its setting time. Therefore, this study was conducted to evaluate the effect of various ratios of liquid to powder of white MTA (WMTA) and addition of DHP on its compressive strength. Methods and Materials: One hundred and twenty samples were prepared with a two-piece stainless steel mold with a height of 6 mm and a diameter of 4 mm in order to evaluate the compressive strength where WMTA was used in 60 samples and DHP in white MTA composition (DHPWMTA) was used in other 60 samples. The compressive strength of WMTA and DHPWMTA was measured in various ratios of liquid to powder including 50, 60 and 70% and at 24 h and 21 days (n=10). Univariate Analysis of Variance test with SPSS 16 software were used to determine the difference between groups. The level of significance was set at 0.05. Results: The maximum and minimum compressive strength of WMTA groups were 63.25±1.96 (50% ratio and 21 days) and 37.79±1.28 (70% ratio and 24 h), respectively. The maximum and minimum compressive strength of DHPWMTA groups were 63.96±1.40 (60% ratio and 21 days) and 37.37±1.62 (70% ratio and 24 h), respectively. The effect of each of factors (type of material, powder to liquid ratio and time) alone were significant on the compressive strength (P<0.05). However, the interactive effect of three factors (type of material, powder to liquid ratio and time) were not statistically significant on compressive strength (P>0.05). Conclusion: Adding 2.5 wt% of DHP to white MTA increased samples compressive strength. Compressive strength in liquid to powder ratios of 50 and 60% compare to 70% and at 21 days compared to 24 h was high. Keywords: Compressive Strength; Disodium Hydrogen Phosphate; Mineral Trioxide Aggregate